Point Break : Surfers and Waves - Brisick, Jamie; Lukacher, Brian; Pettibon, Raymond; David Zwirner (Gallery) (New York : David Zwirner Books, 2022)
"Pettibon is known for his characteristically enigmatic aesthetic and sharply satirical critiques of American culture. Though drenched in cynicism, his work empathizes with the dizzying madness of our own humanity as it engages both so-called high and low culture. Perhaps most poetic among the many motifs present in Pettibon's oeuvre is the surfer. In 1985, Pettibon began his series of surfers and waves--which he continues to work on to this day--popular for depicting a lone surfer silently carving "a line of beauty" along an impossibly large wave. This book spotlights a selection of more than one hundred surfers from the series, from smaller monochromatic works on paper to colorful large-scale paintings applied directly to the wall. For Pettibon's protagonist in these works, surfing exists apart from all else. Momentarily he achieves sublimity on the wave, distant yet synced with turbulent reality. We are forced to confront our own scale: small and feeble in the face of the power of nature, what is beyond our control. Pettibon's lyrical writings on these painted surfaces--both his own and lines taken from literature--reference his own philosophies and the confusions of reality: he critiques and highlights the hypocrisies and vanities of the world he engages. To help navigate, the scholar Brian Lukacher explores art-historical antecedents in Pettibon's work, particularly the seascapes of J. M. W. Turner, and Jamie Brisick, the writer and former professional surfer, examines the Southern California surf and music culture of Pettibon's youth. Professional big wave surfers Emi Erickson and Stephanie Gilmore also describe the sensory experience of conquering the enormous waves depicted in Pettibon's works." --
kunstcatalogus
Keywords: Pettibon, Raymond